A review on biodiesel production from microalgae: Influencing parameters and recent advanced technologies - Zhang, Shiqiu; Zhang, Lijie; Xu, Geng; Li, Fei; Li, Xiaokang (Frontiers in Microbiology, 2022)
Microalgae are the important part of carbon cycle in the nature, and they could utilize the carbon resource in water and soil efficiently. The abilities of microalgae to mitigate CO2 emission and produce oil with a high productivity have been proven. Hence, this third-generation biodiesel should be popularized. This review firstly introduce the basic characteristics and application fields of microalgae. Then, the influencing parameters and recent advanced technologies for the microalgae biodiesel production have been discussed. In influencing parameters for biodiesel production section, the factors of microalgae cultivation, lipid accumulation, microalgae harvesting, and lipid extraction have been summarized. In recent advanced technologies for biodiesel production section, the microalgae cultivation systems, lipid induction technologies, microalgae harvesting technologies, and lipid extraction technologies have been reviewed. This review aims to provide useful information to help future development of efficient and commercially viable technology for microalgae-based biodiesel production.